Full Day School Implementation In Disruption Era As An Effort To Build Creativity And Prophetic Character Of Student In SD Muhammadiyah 18 Surabaya - Ratno Abidin; Asy‟ari Asy‟ari; Uswatun Hasanah (Universitas Muhammadiyah Surabaya, 2020)
Abstract The purpose of this research was to understand the implementation of Full DaySchool system in improving student creativity in school and to examine obstacles and opportunities that exist on its implementation. The approach used in this research was qualitative approach with descriptive method, the subject in this research was student of SD Muhammadiyah 18 Surabaya, research instrument used was guidance interview and documentation study. The data obtained then processed by using data reduction, data display, and interpretation or conclusion. Based on the approach and data processing in the research, then the results were: 1) SD Muhammadiyah 18 Surabaya implemented Full Day School system by providing many extracurricular programs, active and innovative learning from educators; 2) the principals, teachers, and other educators has worked together and helped each other, supported each other in an effort to improve student creativity in SD Muhammadiyah 18 Surabaya; 3) Obstacles faced by teachers or other educators when implementing Full Day School system in SD Muhammadiyah 18 Surabaya was no specific time for home so that the intensive time with the children's family themselves become reduced. So, by using Implementation Full Day School system, it can help to improve students' creativity and profetic character so that it could be applied in daily life outside the school. For schools that will implement Full Day School system, it is expected to provide understanding and explanation of how the mechanism of the system to parents and students so that it can be pplied by students in learning process in school. SD Muhammadiyah 18Surabaya is one of the schools that implements different system with other schoolespecially Full Day School.Keywords: full day school, creativity, student’s prophetic character